Narratives of family members on the suicide of older adults in an Amazonian metropolis - André Luis Sales da Costa; Maximiliano Loiola Ponte de Souza (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To analyze the narratives of family members on the suicide of older adults in Manaus, State of Amazonas, Brazil. METHODS This is a qualitative study of the narratives of eight older adults, who committed suicide in the period of 2001-2012. In the analytic-interpretative process, we have tried to perform the hermeneutic double exercise: to interpret the interpretation of narrators. We have used as theoretical references authors who have investigated suicide from the perspective of gender and its correlations with the sociofamiliar context and with mental disorders. RESULTS The family members would conceive the suicide of the older adults as related to losses, which would occur in a strained sociofamiliar scenario, leading to the appearance of psychopathological situations that, if not properly followed, would result in death. There would also be something inexorable in this sequence of events. The older adults, by the very time of their life, would tend to accumulate losses of different aspects in their trajectory. Their rigor and other relational limitations would simultaneously stress family relationships, favoring conflicts, and hinder adherence to treatment. This model of understanding, which has a wide support in the hegemonic medical-psychological discourse, in a sense minimizes possible self- or heteroaccusations directed at family members. CONCLUSIONS Special attention should be given to identify the older adults who present losses, family conflicts, and signs of psychopathology and who do not follow-up psychosocial care services. Strategies to help older adults handle family conflicts and losses, empowering them, should be developed and made available by intersectoral actions. The adequate treatment of psychopathological conditions should be implanted in a context in which active search mechanisms also existed for older adults who abandoned follow-up. The implementation of these actions is a challenge to be faced in Manaus, State of Amazonas, Brazil, where there is a low availability of psychosocial care services, which are not articulated with specialized care services in tertiary medical conditions, and there is still low coverage by the basic care.